Application of Surface Tension Measurement to Determined Saturated Cooking Oil and Unsaturated Cooking Oil - Dimisa, Adi Ahmad; Hanggara, Indira Prabawati; Rakhmadi, Frida Agung (Proceeding International Conference on Science and Engineering, 2019)
Application surface tension measuring tool to distinguish saturated cooking oil and unsaturated cooking oil has been done. Th is study aims to apply the surface tension measuring tool as an alternative tool for distinguishing saturated cooking oil and unsaturated cooking oil. This study was conducted to distinguish the quality of cooking oil consumption in terms of the number of oil for frying. The method used in this research is the method Torsion Dynamometer conducted in three phases, the first preparation of tools and materials, the second data retrieval, and the third is data processing. The results showed that torsion Dynamometer can be used as a tool to distinguish saturated cooking oil and unsaturated cooking oil. Saturated cooking oil has a value of surface tension ? ± ?? = (1.6604 ±0.01448) dyne/cm, while for unsaturated cooking oil has a value of surface tension ? ± ?? = (1.3492 ± 0.03624) dyne/cm.